Core and Periphery in the European Monetary Union: Bayoumi and Eichengreen 25 Years Later - Nauro F. Campos; Corrado Macchiarelli (London School of Economics and Political Science (LSE), European Institute, 2016)
Bayoumi-Eichengreen (1993) establish a EMU core-periphery pattern using 1963-1988 data. We use same methodology, sample, window length (1989-2015), and a novel over-identifying restriction test to ask whether the EMU strengthened or weakened the core-periphery pattern. Our results suggest the latter.
Keywords: E32; E63; F02; 330; Business cycle synchronization; Structural VAR; European Monetary Union; Core-periphery